If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + -2x * 3 = 5 Reorder the terms for easier multiplication: 21 + -2 * 3x = 5 Multiply -2 * 3 21 + -6x = 5 Solving 21 + -6x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -6x = 5 + -21 Combine like terms: 21 + -21 = 0 0 + -6x = 5 + -21 -6x = 5 + -21 Combine like terms: 5 + -21 = -16 -6x = -16 Divide each side by '-6'. x = 2.666666667 Simplifying x = 2.666666667
| 5(3y-13)-4y=-21 | | -6m-10m=-16 | | -24=5b+b | | -25=-10x+5x | | -8n-n=-18 | | 14x-25=12x+25 | | 2n+2+4n=2 | | 6x-1=5x+6 | | -11k+9k=-20 | | -11-2k=1+k | | 4b+10b=28 | | 2(k-3)=6 | | n-13+5n=-25 | | 4u-8=-28 | | x-7-12x=37 | | (14)-(-4)= | | cos(3x-180)=-1 | | 8(b+29)=24 | | g=3f+13 | | -(x-2)+3x=-3(x+4)+15 | | 6=-3+36 | | 41=-5x+6 | | 6+6n=-2-2n | | x=6y+11 | | t^3-3t^2+3t-2=0 | | 4(v+2)-11=9 | | 5x+8y=775 | | 3.5+y=1.05 | | (7p-8)(8p+9)=0 | | 2(v-5)-15=-3 | | 10+4y=8 | | 6-3x+2(4x-5)=12+2x-(4x+3) |